Personality Development Of Grigory Stepanovitch Smirnov In The Bear Drama By Anthon Chekhov (1888):An Individual Psychological Approach - ROSADI, DARMAWAN; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S. M. Hum (2015)
The object of the research is the drama entitled The Bear by Anthon Chekhov. The major problem of this study is how personality development influences the major character, Grigory Stepanovitch Smirnov, in Anthon Chekhov's The Bear. It is aimed to analyze the drama based on individual psychological approach by Alfred Adler. The type of the study is qualitative research. There are two data sources that the researcher uses, the primary data sources and secondary data sources. The primary data source is the drama itself and the secondary data sources are any information related to study and other books which deal with the study. The techniques of data collection are documentations and library research. Anthon Chekhov wants to tell that everyone has his own personality developments and ways of overcoming them. In the drama, Smirnov has problem with his personality development. It influences his personality in facing the others people. He becomes coarse person and disrespect person